PENERAPAN MEDIA EXE LEARNING UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DIKELAS X SMA NEGERI 9 PEKANBARU - M. Fadli Hidayatullah Hidayatullah; Jimmi Copriady Copriady; Herdini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The research aims to increase student learning achievement on the topic of hydrocarbons in class X Senior High School (SMAN) 9 Pekanbaru. The research were implemented in SMAN 9 Pekanbaru started at beggining May until June 2015. Population of this research is class X1 until class X4. The research is using randomized control group pretest-posttest design. The Analysis technique used normality Liliefors to see same variance samples. After doing normality and Homogeneity test. The samples of this research were the students of class X1 as the experimental class and students of class X3 as the control class. Experimental class is a class that is applied to media Exe Learning while the control class was not. Data analysis technique used is the t-test. Based on data dk (34 +34)-2 =66 and α= 0,05 obtained ttable 1,66 and tcount 4,29. tcount> ttable is 4,29>1.66, means  that the application of media Exe Learning can improve student learning achievement on the topic of hydrocarbons in class X Senior High School (SMAN) 9 Pekanbaru. The category improvement of student achievement at experiment class was high category with N-gain normalized is 0,70. Meanwhile, the category improvement of student achievement in control class was medium category with N-gain normalized is 0,58. Keywords : Achievement of Learning, Exe Learning, Hidrokarbon